Community Perception of Medan City on Brand Medan Rumah Kita (Case Study of Medan Perjuangan Sub-District Community) - Akbar Aldi Kautsar; Ahmad Qorib; Abdul Rasyid (Budapest International Research and Critics University, 2020)
This study is entitled